Validity of Simple Risk Index and Evaluation of Methods andManagement of Acute Coronary Events to Predict Mortality inAcute Coronary Syndrome Patients in Intensive Coronary CareUnit Cipto Mangunkusumo Hospital - Meutia, Rahmah Safitri; Nasution, Sally Aman; Makmun, Lukman H (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Risk stratification is an important part in the management of patients with an Acute Coronary Syndrome (ACS) to avoid overtreatment or undertreatment. Although Simple Risk Index (SRI) and Evaluation of Methods and Management of Acute Coronary Events (EMMACE) have been validated in other countries, no study of its applicability has been performed in Indonesia with different patients’ characteristics. This study aims to obtain the calibration and discrimination performance of SRI and EMMACE to predict 30 days mortality in ACS patients in ICCU of Cipto Mangunkusumo Hospital. Methods. A retrospective cohort study with consecutive sampling was conducted in ACS patients hospitalized in the ICCU Cipto Mangunkusumo hospital between the period of 2003 up to 2010. Data analyzed performed by SPPS program for Windows Version 17. The discrimination performance was explained using a value of area under the receiver-operator curve (AUC) while calibration performance was evaluated using hosmer lemeshow and plot calibration. Results. A total of 922 patients were included in this study consisted of 453 STEMI patients, 234 NSTEMI patients and 235 UAP patients. Simple Risk Index (SRI) score for STEMI had presentable discrimination and calibration performance (AUC= 0,92; R2 = 0,98; and p value= 0,01). Simple Risk Index (SRI) score for overall ACS also showed sufficient performance and calibration discrimination (AUC= 0,87; R2 = 0,99; and p value= 0,52). Meanwhile, EMMACE score in ACS patients showed satisfactory performance discrimination (AUC= 0,87), but the calibration perfomance was not as satisfactory as the SRI score with the calibration plot (R2 )= 0,54 (p value= 0,52). Conclusions. Simple Risk Index (SRI) score shows a satisfactory discrimination and calibration performance both in STEMI and overall ACS patients in predicting mortality of ACS patients in ICCU Cipto Mangunkusumo Hospital. Evaluation of Methods and Management of Acute Coronary Events (EMMACE) score, nonetheless, displays sufficient discrimination performance, but poor performance of calibration.